The titles of King Artashes I according to the Aramaic inscriptions on boundary stones - Margaryan, Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
The titles of Armenian kings of the Artaxiad (Artashesian) dynasty are known mainly owing to coin legends and rather scanty data of ancient historiographers. Artaxiads were usually represented by a short title of ‘king’ or ‘great king’. We see different variants of short titles in Greek: ‘king’, ‘great king’ and the title ‘king of kings’ on the coins of Tigran II (95-55 BC). The same titles were inherited by his son Artavazd II (55-34 BC). The only exception was the coin of Tigran III (20-8 BC) with the legend reading ‘Great king Tigran, Philhellenos and Philopatoros’. These epithets were adopted by him as a sign of his pro-Parthian orientation and anti-Roman stance.